Design of a participatory communicational, educational and cultural proposal in the context of teaching-learning (Revista de Ensino em Artes, Moda e Design, 2020)
This paper aims to discuss the pertinent characteristics for the design of a participatorymodel in the communicational, didactic and cultural spheres. For this, it makes use of bibliographicresearch, guided by a phenomenological look, resonant with the essayistic form ofexpression. It takes different perspectives, of which stand out Martin Buber, Paulo Freire, JuanBustos, Vicente Romano, Victor Ventosa, Kristoffer Haggren and Vilém Flusser - the latter,responsible for the theoretical lens through which we look at design processes. As a result,it indicates the need for a dialogical and horizontal communication, guided by a model thateducates for participation, celebrates the engagement and the discussion of the agreementsand the necessary stimuli for the teaching-learning contexts.